The extent and nature of food advertising to children on Spanish television in 2012 using an international food-based coding system and the UK nutrient profiling model. (August 2016) - Royo-Bordonada, M.Á.; León-Flández, K.; Damián, J.; Bosqued-Estefanía, M.J.; Moya-Geromini, M.Á.; López-Jurado, L.
Abstract: Objective: To examine the extent and nature of food television advertising directed at children in Spain using an international food-based system and the United Kingdom nutrient profile model (UKNPM). Study design: Cross-sectional study of advertisements of food and drinks shown on five television channels over 7 days in 2012 (8am-midnight). Methods: Showing time and duration of each advertisement was recorded. Advertisements were classified as core (nutrient-rich/calorie-low products), non-core, or miscellaneous based on the international system, and either healthy/less healthy, i.e., high in saturated fats, trans-fatty acids, salt, or free sugars (HFSS), according to UKNPM. Results: The food industry accounted for 23.7% of the advertisements (4212 out of 17, 722) with 7.5 advertisements per hour of broadcasting. The international food-based coding system classified 60.2% of adverts as non-core, and UKNPM classified 64.0% as HFSS. Up to 31.5% of core, 86.8% of non-core, and 8.3% of miscellaneous advertisements were for HFSS products. The percentage of advertisements for HFSS products was higher during reinforced protected viewing times (69.0%), on weekends (71.1%), on channels of particular appeal to children and teenagers (67.8%), and on broadcasts regulated by the Spanish Code of self-regulation of the advertising of food products directed at children (70.7%). Conclusions: Both schemes identified that a majority of foods advertised were unhealthy, although some classification differences between the two systems are important to consider. The food advertising Code is not limiting Spanish children's exposure to advertisements for HFSS products, which were more frequent on Code-regulated broadcasts and during reinforced protected viewing time. Highlights: In 2012 there were 7.5 AFD per hour of TV, 64% HFSS, both figures higher than before TV stations subscribed to the PAOS Code. HFSS food advertisements were more frequent on code-regulated broadcasts and during reinforced protected viewing time. The UKNPM is preferable the international food-based coding system for international comparisons of food advertisements.